PENGEMBANGAN SOFT SKILLS DAN RELIABILITY UNTUK MENINGKATKAN KUALITAS PELAYANAN DAN KEPUASAN NASABAH - Agus Budi Purwanto (BBM (Buletin Bisnis & Manajemen), 2015)
This research is motivated declining number of Bank Perkreditan Rakyat (BPR).Decreasing the number of BPR indicate unhealthy condition. In general, this study aimsto determine the model of the development of soft skills and reliability of bankingemployees in order to improve service quality and increase customer satisfaction.Specifically, this study aims to improve the quality of governance, healthy operationalmanagement and professional in the banking world. The model used in this study iscomprised of four variables where the variables in the first stage of soft skills andreliability of the independent variable while the quality of service becomes thedependent variable. Then in the second stage of skill and reliability as an independentvariable, the quality of service as an intervening variable, whereas the variable customersatisfaction as the dependent variable. Research data collection techniques by means ofa questionnaire on BPR customers spread in Semarang systematically arranged withmultiple choice answers are easy to understand. Distribution of the questionnaire bymeans of a direct encounter conducted in the period April to August 2014, with a sampleof some 120 people. Instrument (questionnaire) will go through the stages of validity andreliability. Research data will be analyzed using path analysis (path analysis). Test thestrength of the model using SEM (Structural Equation Modeling). The research provesthat there is a direct positive influence between soft skills and reliability to customersatisfaction. The results also prove that the quality of service is a positive interveningbetween soft skills and reliability to customer satisfaction.Keywords: soft skills, reliability, quality of service, customer satisfaction